SISTEM CROSS FLOW DALAM PEMISAHAN SENYAWA FLAVOR SERUPA DAGING (Meatlike flavor) DARI KACANG HIJAU (Phaseolus radiatus) TERFERMENTASI OLEH Rhizopus oligosporus MELALUI MIKROFILTRASI - Agustine Susilowati; Aspiyanto Aspiyanto (Prosiding SNST Fakultas Teknik, 2010)
Cross-flow Microfiltration System is one of important separation basic using membrane influenced by separation process condition (pressure, flow rate, temperature, time), particles size and molecular weight (MW). The goal of this experiment was to find out composition, type and intensity of flavor compounds produced from autolysate separation of meatlike flavor from fermented mung bean (Phaseolus radiatus L.) through MF membrane at pump motor frequency 20 Hz, room temperature and operation pressure 6 bar for 90 minutes. The experiment results showed that Cross-flow MF System at permeate flux value of 31.83 L/m2.hour was able to separate N-Amino and dissolved protein as meatlike flavor compounds pass through MF membrane more much in permeate, while total solid, fat salt and  protein were rejected and retained more much in concentrate/retentate. Meatlike flavor compounds were dominated by sulphur. MF system was able to separate more much sulphur compounds as meatlike flavor present in permeate than concentrate/retentate. On the permeate was obtained 43 compound of meat analogue dominated by Sulphur-Nitrogen component (71.48%), namely 1,2,3-Triazole,4-flourodinitromethyl-1-methyl (0,01%), 2–Thiopenethiol (0,1%), Chlomethiazole (0,22%), 4-Methyl-5-hydroxyethylthiazole (70,99%), Furfuril-methyl-sulfide (0,11%), 2-Methyl-6-thiopurine (0,05% Area/0,2µg sample), While, other components covered Nitrogen (11), Pyran (4), Furan (5) , Alcohol  (4), Aldehiyde (3), Hidrocarbon (1) and  Ester - organi acid (5).Permeate has potential use as meatlike flavor extract, whereas retentate as concentrate/Hydrolyzed Vegetable Protein (HVP) is used for vegetable food products with meat taste and aroma. Key Words : Meat analog flavor, flavoring reaction, permeate, concentrate/retentate, microfiltration (MF).